Endoscopic Totally Extraperitoneal Repair of Parastomal Hernia: A Case Report - Jiang, Huiyong; Thapa, Dil Momin; Ma, Chun; Cai, Xiangjun; Wang, Mofei (Frontiers in Surgery, 2021)
A parastomal hernia is a type of incisional hernia that occurs in abdominal integuments in the proximity of a stoma. It is a frequent late complication following colostomy. Surgical repair is currently the only treatment option for parastomal hernia. Here we present the case of a 74-year-old patient with parastomal hernia and a history of open surgery treated with a totally extraperitoneal (TEP) endoscopic approach. There was no recurrence of the hernia at the 3-month follow-up. We discuss the feasibility and possible operative approaches for endoscopic repair of parastomal hernia with the TEP technique.